Parametric Design Optimization of Inner Chassis Retarder Bracket Using Finite Element Analysis - Nicky Yongkimandalan; Mochammad Dwi Julianto (Universitas Muhammadiyah Metro, 2026)
The inner chassis retarder bracket is a critical structural component in heavy-duty truck braking systems that transfers braking loads from the electromagnetic retarder to the vehicle chassis. Excessive stress concentration in this component may reduce structural reliability and increase the risk of failure during operation. Although finite element analysis (FEA) has been widely applied to optimize automotive brackets, studies focusing on the parametric optimization of heavy-duty inner chassis retarder brackets through local geometric modification remain limited. This study aims to optimize the structural performance of the right-side inner chassis retarder bracket by investigating the effects of fillet radius and bracket thickness using finite element analysis. Three fillet radius (5, 10, 15, and 20 mm) and thickness levels 10 mm and 16 mm were evaluated for two candidate materials, ASTM A36 structural steel and GGG60 ductile cast iron, resulting in eighteen design configurations. Static structural simulations were performed using ANSYS Workbench 2022 R1 under combined gravitational and retarder torque loading. Structural performance was assessed based on equivalent (von Mises) stress, total deformation, and safety factor. The optimum configuration was obtained using a 15 mm fillet radius and a 16 mm bracket thickness. Compared with the initial design, this configuration reduced the maximum von Mises stress by 62.90% for ASTM A36 steel and 66.01% for GGG60, while decreasing the maximum deformation by 61.19% and 54.91%, respectively. The corresponding minimum safety factor increased by 169.62% for ASTM A36 steel and 335.47% for GGG60, indicating a substantial improvement in structural reliability. These results demonstrate that localized geometric optimization combined with appropriate material selection effectively improves the structural performance of heavy-duty retarder brackets without requiring major modifications to the overall component geometry.